Utilizing Production Sharing Contracts (PSCs) as a Means for the Protection of Indonesia’s Natural Resources - Disemadi, Hari Sutra; Lasmadi, Sahuri (Lentera Hukum, 2019)
Indonesia has the potential to manage natural resources in such a way that social justice, public welfare, and the prosperity of the people is also realized. Contract law is the primary legal umbrella used in efforts to protect natural resources from exploitation. This study uses normative juridical methods that prioritize secondary data as the primary sources. This study shows the form of the legal protection of state assets related to oil and gas management including the government has the right of immunity, the existence of provisions regarding state revenue, state levies, and bonuses and the existence of provisions for contractors to distribute a portion of the production share. Thus, the government uses Production Sharing Contracts (PSC) to enter into oil and gas management agreements with contractors, specifically regarding upstream business activities. The Oil and Gas Law does not elaborate on the meaning of the PSC. Rather, it only states that the PSC is one form of the contracts. Keywords: Production Sharing Contract, State Control, Protection of Natural Resources.